Creating Engaging Flashcard Materials for Young Learners: A Developmental Study on English Language Teaching in Primary Schools - Paldy, Paldy; YR, Sthevaniocy; Baharuddin, M. Rusli; Yunus, Reski Yusrini Islamiyah (Universitas Pendidikan Mandalika, 2025)
Flashcards have long been recognized as effective tools for enhancing vocabulary acquisition, particularly among young learners. However, much of the existing research has focused on secondary or higher education, leaving a gap in understanding their impact on primary school students. This study addresses the need for a deeper exploration of flashcards as a teaching tool in elementary English language instruction. Specifically, the research focuses on the development and evaluation of flashcard-based instructional materials designed to improve vocabulary retention, student engagement, and motivation in young learners. The research utilized the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop flashcards tailored to young learners, emphasizing visually engaging and interactive materials. The findings demonstrated significant improvements in student engagement and vocabulary retention, with high effectiveness scores and positive feedback from both teachers and students. Data were analyzed using descriptive statistics to evaluate the results from the validity, practicality, and effectiveness tests. The findings reveal that the flashcards significantly enhanced students' vocabulary retention, engagement, and motivation, as demonstrated by high scores in effectiveness tests and positive feedback from both teachers and students. Teachers found the materials practical and easy to implement, while students responded favorably to the visual appeal and interactive nature of the flashcards. The findings highlight flashcards as an effective tool for improving vocabulary acquisition and engagement in primary education, offering a practical strategy for early language development.